Biocompatibility of helicoidal multilamellar arginine–glycine–aspartic acid‐functionalized silk biomaterials in a rabbit corneal model. Issue 1 (13th May 2014) - Wang, Liqiang; Ma, Ruijue; Du, Gaiping; Guo, Huiling; Huang, Yifei
Abstract Silk proteins represent a unique choice in the selection of biomaterials that can be used for corneal tissue engineering and regenerative medical applications. We implanted helicoidal multilamellar arginine–glycine–aspartic acid‐functionalized silk biomaterials into the corneal stroma of rabbits, and evaluated its biocompatibility. The corneal tissue was examined after routine hematoxylin–eosin staining, immunofluorescence for collagen I and III, and fibronectin, and scanning electron microscopy. The silk films maintained their integrity and transparency over the 180‐day experimental period without causing immunogenic and neovascular responses or degradation of the rabbit corneal stroma. Collagen I increased, whereas Collagen III and fibronectin initially increased and then gradually decreased. The extracellular matrix deposited on the surface of the silk films, tightly adhered to the biomaterial. We have shown this kind of silk film graft has suitable biocompatibility with the corneal stroma and is an initial step for clinical trials to evaluate this material as a transplant biomaterial for keratoplasty tissue constructs. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 204–211, 2015.